Retraction: A surfactant-free co-assembly route to fabricate 2D TiO2–WO3 composite inverse opal films for photochromic applications. (13th October 2015) - Zhen, Hongyu; Li, Kan
Abstract : Retraction of 'A surfactant-free co-assembly route to fabricate 2D TiO2 –WO3 composite inverse opal films for photochromic applications' by Hongyu Zhen et al., New J. Chem., 2014, 38, 4041–4044.